Expression and identification of C5a and its receptor (C5aR) as a diagnostic marker for benign mammary tumour - Bachek, Noor Farhana (2016)
Complement system is a part of innate and adaptive immune system that act as a ‘first line of defense’ against infections and immune complex diseases. There are three main pathways activate the complement system; classical pathway, alternative pathway and lectin pathway. Although these three pathways are activated by different triggers and stimuli, these step-wise activations eventually lead to the cleavage of the C5 molecule and generating C5a and C5b. C5a is a 74 amino acids sequence protein fragment derived from the cleavage of complement component by protease C5-convertase. C5a was first described as a classical anaphylatoxin and a highly inflammatory peptide and have been found in the serum of patient with inflammatory disorder such as cancer. However, the possible involvement between C5a anaphylatoxin and tumour progression is not yet well understood. In this study, we assessed the expression of C5a/C5aR in the EMT6 cells and measured the expression and up-regulation of C5a/C5aR in both mRNA and protein levels. We demonstrate that the expression of C5a/C5aR is up-regulated in EMT6 cells and can be potentially use as a screening biomarker for mammary cancer. The first part of study was the determination of the expression of C5a/C5aR mouse mammary cancer cells by Immunofluorescence staining using compatible antibodies followed by Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) of EMT6 cell. The study was further analyzed by treating the EMT6 cells using three types of treatment; EP54 (C5a agonist peptide), PMX205 (C5a antagonist peptide) and control drug of tamoxifen. Thus, the magnitude of the C5a/C5aR expression of the treated EMT6 cell was measured by quantitative Real-Time Polymerase Chain Reaction (qPCR). The validation assessment of C5a/C5aR as a screening biomarker was determined using cell cytotoxicity assay of MTT and enzyme-linked immunosorbent assay (ELISA) using C5a antibodies. The immunofluorescence staining of EMT6 cells indicate the presence of C5aR receptors located on the membrane of EMT6 cells. This finding is further justified the C5a receptor expression of EMT6 cells in mRNA level with detection of a single band using RT-PCR. The relative quantification of C5a/C5aR magnitude of treated EMT6 cell showed the reduction C5a/C5aR level in PMX205 as compared to EP54 with the fold change of 0.307±0.2885 and 0.625±1.2109, respectively. This findings showed similar pattern in validation assessment of C5a/C5aR where PMX205 reduced the level of C5a in MTT and ELISA as compared to EP54. Overall, the viability of EMT6 cells treated with PMX205 showed a greater cell inhibition as compared to EP54 throughout the time points. The value recorded for PMX205 on 24, 48 and 72 hours treatment were (0.1069±0.016), (0.1066±0.008) and (0.0543±0.001), respectively. As for EP54, the value recorded for 24, 48 and 72 hours treatment were (0.1137±0.03), (0.1164±0.04) and (0.0561±0.02), respectively. While on ELISA, the PMX205 exhibited a reduced C5a protein level (0.1713±0.08) in comparison to EP54 (0.2511±0.183). In conclusion, these data suggest that there EMT6 cells indeed exhibit the C5a/C5aR expression and have the capacity to generate C5a due to magnitude and up-regulation of C5a concentration detected in both mRNA and protein levels. This study also exhibit the potential pharmacological blockage using C5a antagonist decreased the level of C5a in the mammary cancer and hence, C5a/C5aR has a potential utility as a screening biomarker for mammary cancer.